Visual literacy in instructional design programs. Issue 2 (2nd April 2016) - Ervine, Michelle D.
Abstract: In this technologically advanced environment, users have become highly visual, with television, videos, web sites and images dominating the learning environment. These new forms of searching and learning are changing the perspective of what it means to be literate. Literacy can no longer solely rely on text-based materials, but should also incorporate digital images and sounds. Higher education seems to be lagging behind with incorporating visual literacy into their academic programs. This paper explores visual literacy, the digital native, and the importance of integrating visual literacy into our learning curriculum, especially in instructional design programs.